Sequência didática para auxiliar na produção do gênero textual relatório técnico científico na educação profissional e tecnológica de nível médio - França, Analucia da Silva (2021)
The difficulty in producing the textual genre scientific technical report is common among students. However, just few studies are dedicated to this problem. This research aims to analyze the contributions of the development of a didactic sequence to assist in the production of the textual genre scientific technical report in the Educação Profissional e Tecnológica de Nível Médio – EPTMN. This is a field research of qualitative approach that was developed with concluding students of integrated technical high school and teachers of the Instituto Federal do Amazonas - IFAM, Presidente Figueiredo Campus. As instruments of data collection we used questionnaires with open and closed questions and reports from the research group on social media. The closed questions in the questionnaires, although quantitative, were analyzed qualitatively. The open-ended questions and reports from the WhatsApp Research Group (GPW) were analyzed using Bardin's (2016) Content Analysis technique. Workshops were conducted, using a didactic sequence, based on the model proposed by Dolz and collaborators (2004), with adaptations, to guide students regarding the production of the textual genre scientific technical report and evaluate the contributions of a specific didactic sequence for this textual genre, that was subsequently improved and transformed into an educational product. The results of this research showed that the main contributions of the development of a didactic sequence to assist in the production of the textual genre scientific technical report in EPTMN is in familiarizing students with this textual genre; to deep and expand their knowledge about this textual genre and its production; and offer a set of ordered activities with suggestions for materials that will guide and facilitate the production of this textual genre. As an outcome of this research, we present the educational product "didactic sequence to assist in the production of the textual genre scientific technical report".